2013
DOI: 10.1038/ncomms3223
|View full text |Cite|
|
Sign up to set email alerts
|

Probing the nature of gold–carbon bonding in gold–alkynyl complexes

Abstract: Homogeneous catalysis by gold involves organogold complexes as precatalysts and reaction intermediates. Fundamental knowledge of the gold–carbon bonding is critical to understanding the catalytic mechanisms. However, limited spectroscopic information is available about organogolds that are relevant to gold catalysts. Here we report an investigation of the gold–carbon bonding in gold(I)–alkynyl complexes using photoelectron spectroscopy and theoretical calculations. We find that the gold–carbon bond in the ClAu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 51 publications
3
47
0
Order By: Relevance
“…The strong Au-C bond in ClAu-CCH − was shown to be due to the polarization effect of the electronegative Cl: the Au-C bond in FAu-CCH − was shown to be even stronger, while that in IAu-CCH − was weaker. 10 The calculated Au-C distance of 1.95 Å in AuC 2 − (Table IV) is the same as that in ClAu-CCH − . But the Au-C stretching frequency in AuC 2 − is lower than that in ClAu-CCH − .…”
Section: Comparison Of the Chemical Bonding In Au-cc − With Clau-cmentioning
confidence: 70%
See 1 more Smart Citation
“…The strong Au-C bond in ClAu-CCH − was shown to be due to the polarization effect of the electronegative Cl: the Au-C bond in FAu-CCH − was shown to be even stronger, while that in IAu-CCH − was weaker. 10 The calculated Au-C distance of 1.95 Å in AuC 2 − (Table IV) is the same as that in ClAu-CCH − . But the Au-C stretching frequency in AuC 2 − is lower than that in ClAu-CCH − .…”
Section: Comparison Of the Chemical Bonding In Au-cc − With Clau-cmentioning
confidence: 70%
“…10 The Au-C bond strength in ClAu-CCH − was shown to be extremely high (5.01 eV for ClAu-CCH − to dissociate to ClAu + CCH − calculated at the CCSD(T) level), even higher than that in ClAuCN − . More surprisingly, it was found that the single Au-C bond in ClAu-CCH − was stronger than the Au=C and Au≡C multiple bonds, revealing an inverse correlation between bond strength and bonder order.…”
Section: Comparison Of the Chemical Bonding In Au-cc − With Clau-cmentioning
confidence: 96%
“…Although these problems are well known, the literature is full of examples where dissociation energies are used as bond strength descriptors for the stable, nondissociated molecule. In a recent publication Lai‐Sheng Wang and coworkers studied the nature and strength of the gold–carbon bond in several gold catalysts ).…”
Section: Bond Strengthmentioning
confidence: 99%
“…In addition, P-Au-NPs don't show stretching vibration peak of =C-H at 3040 cm À1 compared with VPA sample, confirming that the reduction of HAuCl 4 originates from the reduce capability of C¼C bond in VPA. The organogold chemistry have demonstrate the existence of Au-C bond [30]. Thus, we infer that the weak peak at 289 eV maybe originate from Au-C bond (Fig.…”
Section: Physicochemical Characterization Of the P-au-npsmentioning
confidence: 76%